Perceived guideline clarity impacts guideline-concordant care for breast cancer screening in women age 40-49 - Michelle B. Nadler; Ann Marie Corrado; Brooke E. Wilson; Alexandra Desnoyers; Eitan Amir; Noah Ivers; Laura Desveaux (BMC, 2023)
Abstract Background Canadian and US Task Forces recommend against routine mammography screening for women age 40-49 at average breast cancer risk as harms outweigh benefits. Both suggest individualized decisions based on the relative value women place on potential screening benefits and harms. Population-based data reveal variation in primary care professionals (PCPs) mammography rates in this age group after adjusting for sociodemographic factors, highlighting the need to explore PCP screening perspectives and how this informs clinical behaviours. Results from this study will inform interventions that can improve guideline concordant breast screening for this age group. Methods Qualitative semi-structured interviews were performed with PCPs in Ontario, Canada. Interviews were structured using the theoretical domains framework (TDF) to explore determinants of breast cancer screening best-practice behaviours: (1) risk assessment; (2) discussion regarding benefits and harms; and (3) referral for screening. Analysis Interviews were transcribed and analyzed iteratively until saturation. Transcripts were coded deductively by behaviour and TDF domain. Data that did not fit within a TDF code were coded inductively. The research team met repeatedly to identify potential themes that influenced or were important consequences of the screening behaviours. The themes were tested against further data, disconfirming cases, and different PCP demographics. Results Eighteen physicians were interviewed. The theme of perceived guideline clarity (a lack of clarity on guideline-concordant practices) influenced all behaviours and moderated the extent to which the risk assessment and discussion occurred. Many were unaware of how risk-assessment factored into the guidelines and/or did not perceive that a shared-care discussion was guideline-concordant. Deferral to patient preference (screening referral without a complete discussion of benefits and harms) occurred when the PCPs had low knowledge regarding harms and/or if they experienced regret (TDF domain: emotion) resulting from prior clinical experiences. Older providers described patient's influence impacting their decisions and physicians trained outside Canada, practicing in higher-resourced areas, and female physicians described being influenced by beliefs about consequences of benefits of screening. Conclusion Perceived guideline clarity is an important driver of physician behaviour. Improving guideline concordant care should start by clarifying the guideline itself. Thereafter, targeted strategies include building skills in identifying and overcoming emotional factors and communication skills important for evidence-based screening discussions.